2000
DOI: 10.1002/jccs.200000124
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents from Annona Glabra III

Abstract: Twenty compounds including a dioxoaporphine, annobraine (1); two oxoaporphines, liriodenine (2) and lysicamine (3); five aporphines, (‐)‐nornuciferine (4), (‐)‐anonaine (5), (‐)‐N‐formylanonaine (6), (‐)‐asimilobine (7) and (+)‐nordomesticine (8); one proaporphine, (+)‐stepharine (9); two protoberberines, (‐)‐kikemanine (10) and dehydrocorydalmine (11); one azaanthraquinone, 1‐aza‐4‐methyl‐2‐oxo‐1,2‐dihydro‐9,10‐anthracenedione (12); two amides, N‐trans‐feruloyltyramine (13) and N‐p‐coumaroyltyramine (14); one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(18 citation statements)
references
References 34 publications
1
16
0
1
Order By: Relevance
“…This indicated that a tworing system remains to be accommodated. Thus, a trans-decalin system of rings A and B was deduced from the 13 Abstract A new clerodane diterpenoid 16-hydroxycleroda-13-ene-15,16olide-3-one (1) was isolated from the bark of Polyalthia longifolia var. The 13 C-and DEPT NMR analyses indicated twenty carbon resonances attributed to five quaternary, three methine, six methylene, and four methyl carbons.…”
mentioning
confidence: 99%
“…This indicated that a tworing system remains to be accommodated. Thus, a trans-decalin system of rings A and B was deduced from the 13 Abstract A new clerodane diterpenoid 16-hydroxycleroda-13-ene-15,16olide-3-one (1) was isolated from the bark of Polyalthia longifolia var. The 13 C-and DEPT NMR analyses indicated twenty carbon resonances attributed to five quaternary, three methine, six methylene, and four methyl carbons.…”
mentioning
confidence: 99%
“…The crude extract was suspended into water and partitioned with CHCl 3 to afford CHCl 3 layer and water solubles, respectively. Purification of the CHCl 3 soluble fraction by column chromatography yielded roemerine ( 1 , 13.7 mg) [13], cyathisterol ( 2 , 10.8 mg) [14], liriodenine ( 3 , 379 mg) [10], oliveroline ( 4 , 2.1 mg) [15], ushisurine ( 5 , 230 mg) [10], dihydrocostunolide ( 6 , 3.6 mg) [16], (−)- N -formylanonaline ( 7 , 7.9 mg) [15], 6α-hydroxy-β-sitostenone ( 8 , 4.7 mg) [15], ferulic acid ( 9 , 5.9 mg) [17], β-sitosterone ( 10 , 10.3 mg) [18], β-stigmastenone ( 11 , 11.5 mg) [18], costunolide ( 12 , 1.2 mg) [19], β-sitostanone ( 13 , 1.6 mg) [18], dehydroroemerine ( 14 , 1.9 mg) [20], ferruginol ( 15 , 1.2 mg) [21], sugiol ( 16 , 1.3 mg) [22], ( 11 S )-1-oxoedudesm-4(14)-eno-13, 6α-lactone ( 17 , 1.1 mg) [23], dihydroreynosin ( 18 , 1.2 mg) [23], romucosine ( 19 , 1.6 mg) [24], 11,13-dihydrosantamarin ( 20 , 0.8 mg) [25], 2-methylanthraquinone ( 21 , 1.5 mg) [26], methyl 22-feruloyloxydocosanoate ( 22 , 1.9 mg) [27], annonbraine ( 23 , 1.1 mg) [28], ferulic aldehyde ( 24 , 0.7 mg) [29], secoroemerine ( 25 , 0.6 mg) [30], blumenol A ( 26 , 1.3 mg) [31], (−)- N -formyldehydroanonaline ( 27 , 1.7 mg) [32], 6α,7-dehydroanonaline ( 28 , 0.9 mg) [33], N - trans -feruloyltyramine ( 29 , 1.0 mg) [27], N - trans -feruloylmethoxytyramine ( 30 , 1.1 mg) [17], syringaresinol ( 31 , 1.7 mg) [34], cepharadione-A ( 32 , 0.9 mg) [35], aristolic acid II ( 33 , 0.8 mg) [17], O -acetyl-ushinsunin ( 34 , 0.9 mg) [10], (+)-isolaricirensinol ( 35 , 1.6 mg) [34], northalifoline ( 36 , 1.5 mg) [35], cassyformin ( 37 , 2.0 mg) [36], 3-[2-(4-hydroxy-3-methoxyphenyl)-3-hydroxymethyl-7-methoxy-2,3-dihydro-1-benzofuran-5-yl]propan-1-ol ( 38 , 1.7 mg) [37], dehydrodiconiferyl alcohol ( 39 , 0.8 mg) [38], divanillyl tetrahydrofuran ( 40 , 1.9 mg) [39], methyl vanillate ( 41 , 0.7 mg) [24], noroliveroline ( 42 , 0.7 mg) [40], 1-acetyl-β...…”
Section: Resultsmentioning
confidence: 99%
“…We also reported the crystal structures of several alkaloid from the mother liquor [9][10][11][12][13]. N-formylanonaine, the very common alkaloids with Nformylaporphine skeletons was discovered in families of Annonaceae [14][15][16], Menispermaceae [17,18], and Magnoliaceae [19]. However, it is reported from the species of Sinomenium acutum for the first time.…”
Section: Discussionmentioning
confidence: 95%